Mindfulness Training in Primary Schools Decreases Negative Affect and Increases Meta-Cognition in Children - Vickery, Charlotte E.; Dorjee, Dusana (Frontiers in Psychology, 2016)
Studies investigating the feasibility and impact of mindfulness programs on emotional well-being when delivered by school teachers in pre-adolescence are scarce. This study reports the findings of a controlled feasibility pilot which assessed acceptability and emotional well-being outcomes of an 8-week mindfulness program (Paws b) for children aged 7–9 years. The program was delivered by school teachers within a regular school curriculum. Emotional well-being was measured using self-report questionnaires at baseline, post-training and 3 months follow-up, and informant reports were collected at baseline and follow-up. Seventy one participants aged 7–9 years were recruited from three primary schools in the UK (training group n = 33; control group n = 38). Acceptability of the program was high with 76% of children in the training group reporting ‘liking’ practicing mindfulness at school, with a strong link to wanting to continue practicing mindfulness at school (p < 0.001). Self-report comparisons revealed that relative to controls, the training group showed significant decreases in negative affect at follow-up, with a large effect size (p = 0.010, d = 0.84). Teacher reports (but not parental ratings) of meta-cognition also showed significant improvements at follow-up with a large effect size (p = 0.002, d = 1.08). Additionally, significant negative correlations were found between changes in mindfulness and emotion regulation scores from baseline to post-training (p = 0.038) and baseline to follow-up (p = 0.033). Findings from this study provide initial evidence that the Paws b program in children aged 7–9 years (a) can be feasibly delivered by primary school teachers as part of the regular curriculum, (b) is acceptable to the majority of children, and (c) may significantly decrease negative affect and improve meta-cognition.